DEVELOPMENT OF RISK ASSESSMENT SYSTEM FOR CONCRETE STRUCTURES CONSTRUCTION IN VIETNAM AND COMPARISON BETWEEN JAPAN & VIETNAM - PHAN, Quy Thanh; NOGUCHI, Takafumi (SOCIOTECHNICA, 2011)
Risk management for overseas construction projects has become an extremely important subject. Based on the situation, "Development of Risk assessment system for Concrete Structures Construction in Vietnam" has been conducted. This research content three research investigations to collect actual data concerning the probability & cost of occurred failure, the factor of the accident related formwork and methods for reduce & deal with the failure in concrete construction in Vietnam. This paper presents the first investigation process and result. As the result of the first investigation, Event Tree Analysis was conducted by using some case of risk curves to identify and evaluate the sequence of events in the failures. Comparison was done between the results in Vietnam and those in Japan. As the result, mostly risk in concrete construction in Vietnam is 4 times higher than those in Japan.